Development of a novel konjac glucomannan/soy protein isolate/fatty acid composite film: Insights into the structure, properties and interaction mechanism - Xiumei Wang; Qingyu Song; Lulu Li; Wenting Lin; Xiaoxu Zhao; Jie Pang (PLoS ONE, 2026)
The preparation, structural characterization and properties analysis of novel konjac glucomannan (KGM)/soy protein isolate (SPI)/fatty acid (KS-FA) films were carried out in this paper. KS-FA films exhibited higher crystallinities than KS film. Moreover, incorporating fatty acids significantly affected the surface roughness and morphologies of KS film. KS-FA films had significantly (p < 0.05) higher water contact angle values than KS film. The rheological properties of the film-forming solution, thermal stabilities, mechanical, water vapor barrier and water resistance properties of KS film were also improved after incorporating appropriate concentrations of fatty acids. There were a 21.3-percent increase of glass transition temperature value, a 17-percent increase of water contact angle value, a 14.5-percent decrease of water solubility value, a 43-percent decrease of water vapor permeability value, a 1.08-fold increase of tensile strength value, and a 1.52-fold increase of elongation at break value in KS film with 0.7% lauric acid when compared with those of KS film. Furthermore, molecular docking and fourier transform infrared spectroscopy analyses suggested that KS-FA films were formed through hydrogen bonds and hydrophobic interactions. These findings highlight fatty acid-modified KGM/SPI films as promising biodegradable food packaging materials.